A ação de treinadores de judô voltada à profissionalização: uma investigação-ação em âmbito internacional - Olivio, José Alfredo [UNESP] (2020)
This work aimed to present an action-research of two Physical Education professionals, judo coaches, at the 29th Summer Universiade of Taipei in 2017. The action-research can be defined as a set of processes involving actions and their subsequent understandings. The analysis showed that sporting performance can be achieved more effectively from an effective application of scientific knowledge, whether in athletes’ diagnostics, logistics, pre-competitive and competitive actions. It is hoped with this article that, at least in judo, a debate will begin to promote the development of professional procedures for sport coaches from reflexive and applied situations